Election 2007 The Shift to Limited Preferential Voting in Papua New Guinea - May, R.J; Anere, Ray; Haley, Nicole; Wheen, Katherine (ANU Press, 2013)
Papua New Guinea's general election in 2007 attracted particular interest for several reasons. Not only did it follow what was widely acknowledged as the country's worst election ever, in 2002 (in which elections in six of the country's 109 electorates were declared to be 'failed elections'), it was the first general election to be held under a new limited preferential voting system. It also followed the first full parliamentary term under the Organic Law on the Integrity of Political Parties and Candidates, which had been introduced in 2001 in an attempt to strengthen political parties and create a greater degree of stability in the national parliament, and was the first to embrace a 'whole-of-government' approach to electoral administration, through an Interdepartmental Electoral Committee. This volume provides an analysis of the 2007 election, drawing on the work of a domestic monitoring team organized through the National Research Institute, and several visiting scholars. It addresses key issues such as voter education, electoral administration, election security, the role of political parties, women as candidates and voters, the shift to limited preferential voting, and HIV transmission, and provides detailed accounts of the election in a number of open and provincial electorates. It is generally agreed that the election of 2007 was an improvement on that of 2002. But problems of electoral administration and voting behaviour remain. These are identified in this volume, and recommendations made for electoral reform.